Bibliometric evaluation of 2011–2021 publications on hydrogen sulfide in heart preservation research - Chen, Mingcong; Zhou, Qian; Wu, Fei; Sun, Fang; Meng, Yang; Zhang, Yang; Zhao, Mingyi (Frontiers in Cardiovascular Medicine, 2023)
Background: Hydrogen sulfide is known for its unpleasant odour and severe toxicity. However, an in-depth study of hydrogen sulfide showed it can be used as an important messenger, which can play important physiological and pathological roles in vitro and in vivo. In recent years, the application of H2S in the field of cardiac preservation has attracted the interest and attention of scholars worldwide. Hydrogen sulfide plays an effective protective role in cardiac ischaemia/reperfusion injury through antioxidant, anti-inflammatory, and antiapoptotic mechanisms. Objective: The purpose of this paper is to analyse the current scientific achievements on the application of hydrogen sulfide in the field of cardiac preservation and to provide new ideas for further research. Methods: TS=("hydrogen sulfide" OR "hydrogen sulfide") AND TS=("cardiac" OR "heart" OR "myocardium" OR "hearts") AND TS=( "reperfusion" or "transplantation" or "implanted" or "transplant" or "implantation" or "migration" or "preservation" or "grafting" OR "ischaemia" OR "perfusion" or "conservation" or "preserve" or "reservation" ) AND DT= (Article OR Review) AND LA=(English) were used as a search strategy for data collection from the Science Citation Index-Expanded database of the Web of Science Core Collection. CiteSpace 5.8. R3 and Microsoft Office Excel 2019 were used for data analysis. Results: A total of 429 related papers were included, and the total number of papers showed a fluctuating upwards trend. We used CiteSpace 5.8. R3 and Microsoft Excel 2019 to evaluate and visualize the results, analysing institutions, countries, journals, authors, cocited references and keywords. Conclusions: As increasing evidence shows that hydrogen sulfide plays an indispensable role in the field of cardiac preservation, its mechanistic research and clinical application may become the main focus of future research.